IMPLEMENTASI PEMBELAJARAN TEMATIK KELAS 2 PADA MASA PANDEMI COVID-19 DI MI NU SUMBERPASIR MALANG - Nurul Muawana; Fita Mustafida; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The arrival of the Covid 19 virus outbreak at the beginning of 2020 became a new challenge in the world of education where learning which was originally in the classroom changed drastically to being in their respective homes. The online learning process between teachers and learning is not in the same room and location because they are both separate. In contrast to the face-to-face learning process during the learning process, online learning relies heavily on internet technology in carrying out the learning process. In carrying out online learning there are several obstacles that must be faced, some do not have mobile phones, are constrained by data packets and signal networks. The method used in this research is a qualitative method with the type of case study research. The results of the study show that the teacher's thematic learning planning uses a learning implementation plan and its implementation uses the whatsapp application for the problem of online learning, which is in the communication tool.